Monetary enigmas in the local law. The mencales and maravedís in the castillian charters - Oliva Manso, Gonzalo (Revista General de Información y Documentación, 2016)
The history of money in medieval Castile has always been influenced by the not always harmonious coexistence between two very different monetary systems. One based on silver, from Europe, another focused on gold, of Arabic origin. The need to connect and establish equivalence between them soon became a need, especially when gold coins increased its variants. In this complex situation mencales and maravedis are mentioned together in many charters: Zorita, Uclés, Cuenca,... without leaving its nature entirely clear. This article compares these references and analyse the equivalences between them. As a culmination of work we can say that the maravedis cited in each text correspond with golden coins of different weight and value while the mencal is identified with a weight of gold that relates them.